2017
DOI: 10.1002/biof.1380
|View full text |Cite
|
Sign up to set email alerts
|

The combination of digoxin and GSK2606414 exerts synergistic anticancer activity against leukemia in vitro and in vivo

Abstract: Digoxin is a member of cardiac glycosides and recent studies show that digoxin plays anticancer role in several types of cancer. However, the anticancer effects and mechanism of digoxin in leukemia is largely unknown. Her, our data show that digoxin treatment significantly inhibits leukemia cell viability. In addition, digoxin treatment significantly induced apoptosis and G2/M cell cycle arrest in leukemia cells. Furthermore, we demonstrated that digoxin treatment inactivate that oncogenic pathway Akt/mTOR sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In a P301L tau mouse frontotemporal dementia model, PERK inhibition allowed recovery of protein synthesis and prevented neuronal loss, reducing behavioral symptoms [132]. The PERK inhibitors were also effective in mouse models of prion disease [130], PD [131], TBI [135] and AD [133] and in models of bone cancer and leukemia [198,199]. However, the GSK compounds were reported to also have off-target effects [134].…”
Section: Perk Pathway Inhibitionmentioning
confidence: 99%
“…In a P301L tau mouse frontotemporal dementia model, PERK inhibition allowed recovery of protein synthesis and prevented neuronal loss, reducing behavioral symptoms [132]. The PERK inhibitors were also effective in mouse models of prion disease [130], PD [131], TBI [135] and AD [133] and in models of bone cancer and leukemia [198,199]. However, the GSK compounds were reported to also have off-target effects [134].…”
Section: Perk Pathway Inhibitionmentioning
confidence: 99%
“…Digoxin ( 133 ), isolated originally from Digitalis lanata Ehrh. (Plantaginaceae), has been long used to treat congestive heart failure through inhibition of the α subunits of Na + /K + -ATPase. , Recent studies showed that digoxin ( 133 ) is cytotoxic toward Raji and NAMALWA human Burkitt’s lymphoma and K562 and THP-1 human leukemia cells. , Tumor growth was inhibited when 4-week-old male BALB/c nude mice bearing Raji lymphoma xenografts were treated (i.p.) daily with digoxin ( 133 ) (2 mg/kg) for 3 weeks .…”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…Also, leukemia growth was suppressed synergistically by a combination treatment of digoxin ( 133 ) and the unfolded protein response signaling inhibitor GSK2606414 when 6-week-old female nude mice inoculated with K562 cells were treated (i.p.) with digoxin ( 133 ) (2 mg/kg), GSK2606414 (50 mg/kg), or digoxin (2 mg/kg) plus GSK2606414 (50 mg/kg) every 3 days for 4 weeks …”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…Analyses of the FAERS and JMDC claims databases revealed significant inverse signals between digoxin and the four cancers. Previous basic research studies have supported the potential value of cardiac glycosides, such as digoxin, as chemotherapeutic candidates 2528 . At the mechanistic level, several different pathways have been suggested to be responsible for mediating cytotoxic effects, including calcium-dependent activation of caspases and other hydrolytic enzymes 5,29 , generation of reactive oxygen species 30 , topoisomerase inhibition 31 and interference of signal transduction pathways, such as Src, epidermal growth factor receptor, p21 and hypoxia inducible factor-1α 2,4 .…”
Section: Discussionmentioning
confidence: 97%